IMPLEMENTATION MAKASSAR CITY DAYA TERMINAL PUBLIC TRANSPORT CONTROL POLICY - Marhana Aliagus; Andi Cudai Nur; Didin Halim (Jurnal Aktor, 2026)
This paper aims to determine the Implementation of Public Transportation Control at Daya Terminal in Makassar City along with supporting and inhibiting factors of the Implementation of Public Transportation Control Policy at Daya Terminal in Makassar City. This study uses a qualitative approach and produces descriptive data. Data collection is carried out by means of observation, interviews and documentation. Data are processed using three simultaneous activity flows, namely data reduction, data presentation and drawing conclusions/verification. The results of the study indicate that the Implementation of Public Transportation Control at the Daya Terminal in Makassar City in this case has been implemented but is still less than optimal. There are 4 dimensions that are considered in viewing the implementation of the policy, namely in terms of disposition, communication, resources and bureaucratic structure. Of the four indicators, the obstacles in the application and implementation are disposition and resources because they have not been optimally implemented in the control of public transportation at the Daya Terminal in Makassar City. The causal factors that are obstacles include the lack of public awareness, facilities and infrastructure, and driver awareness regarding the policy of controlling public transportation at the Daya Terminal in Makassar City.